2020
DOI: 10.3390/plants9111612
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Exploration of Channel Type and Efflux Silicon Transporters and Silicification Proteins in 80 Sequenced Viridiplantae Genomes

Abstract: Silicon (Si) accumulation protects plants from biotic and abiotic stresses. It is transported and distributed within the plant body through a cooperative system of channel type (e.g., OsLsi1) and efflux (Lsi2s e.g., OsLsi2) Si transporters (SITs) that belong to Noduline-26 like intrinsic protein family of aquaporins and an uncharacterized anion transporter family, respectively. Si is deposited in plant tissues as phytoliths and the process is known as biosilicification but the knowledge about the proteins invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
(141 reference statements)
3
6
0
Order By: Relevance
“…Previous studies found that the Lsi2 protein in plants is localized in the plasma membrane, featuring 9-11 TMDs, with extracellular N-and extracellular/cytoplasmic C-terminus regions (Vivancos et al 2016;Vatansever et al 2017;Nawaz et al 2020). Similarly, we identified 9-11 TMDs in the putative poplar Lsi2 homologs except Potri.017G141950.1, which contained five TMDs (Supplementary Fig.…”
Section: Si Efflux Transportersupporting
confidence: 65%
See 4 more Smart Citations
“…Previous studies found that the Lsi2 protein in plants is localized in the plasma membrane, featuring 9-11 TMDs, with extracellular N-and extracellular/cytoplasmic C-terminus regions (Vivancos et al 2016;Vatansever et al 2017;Nawaz et al 2020). Similarly, we identified 9-11 TMDs in the putative poplar Lsi2 homologs except Potri.017G141950.1, which contained five TMDs (Supplementary Fig.…”
Section: Si Efflux Transportersupporting
confidence: 65%
“…Similar to OsLsi1/OsLsi6, the distance between the two NPA motifs in PtLsi1 is 108 AA. The channel-type SITs in plants have six transmembrane domains (TMDs) (Wallace and Roberts 2004;Ma et al 2006;Nawaz et al 2020). We also found six TMDs in PtLsi1 (Fig.…”
Section: Channel-type Si Influx Transporters (Sits)mentioning
confidence: 99%
See 3 more Smart Citations